The reduced expression of trimethylation of histone H3 at lysine 27 in primary cutaneous mucinous carcinoma - Shu-Hao Li; Chien-Chun Chiou; Chien-Chin Chen (Wolters Kluwer Medknow Publications, 2023)
Primary cutaneous mucinous carcinoma (PCMC) is rare, and its carcinogenesis is unclear. Trimethylation of histone H3 at lysine 27 (H3K27me3) is a key regulator in chromatin remodeling-controlled transcription. Focusing on the epigenetic mechanism, we aimed to investigate the expression of H3K27me3 in PCMC by immunohistochemistry. A retrospective cohort of PCMC patients from a tertiary hospital in Taiwan was enrolled to evaluate the clinicopathologic features, treatment outcome, and protein expression. Immunohistochemistry for H3K27me3 was performed on all PCMCs and a comparison group of colonic mucinous adenocarcinoma and pure mucinous carcinoma of the breast. The percentage of H3K27me3-negative tumor cells was calculated and analyzed. Three patients with PCMC were recruited. All PCMCs were solitary and slow growing, arising from the head-and-neck region. All PCMCs had tumor excision without local recurrence or metastasis. The loss of H3K27me3 expression was significant in PCMCs (mean ± standard deviation [SD]: 21.0% ± 6.6%) compared to other mucinous carcinomas (mean ± SD: 3.8% ± 1.7%) (P = 0.019). In conclusion, we report a reduction in H3K27me3 expression in PCMC. In contrast, H3K27me3 expression is retained or mildly reduced in other mucinous carcinomas. This is the first study to indicate a possible role of epigenetic events in the pathobiology of PCMC.